Relevance of Cognitive Learning Theory in Student Concept Formation: Relevansi Teori Belajar Kognitif dalam Pembentukan Konsep Siswa - Saputri, Rizka Sofyan; Witdanarko , Fajar; Sunarsih, Tiwik; Subrata, Heru; Wiryanto, Wiryanto (Universitas Muhammadiyah Sidoarjo, 2024)
Learning is an obligation for students. Learning contains theories or subjects that can be used as a reference. One learning theory is cognitive learning theory. This theory prioritizes processes rather than results. The formation of students' concepts can be interpreted as how students understand themselves. Because, there are still some students who cannot understand themselves and still look to other people. This research aims to determine the relevance of cognitive learning theory in forming students' concepts. The method used is a qualitative research method. This method uses narrative in analyzing data and the data is descriptive. The design of this research is library research which uses a literature review to obtain data. Data comes from journal articles, previous publications, and books. The results of this research indicate that there is a connection between cognitive learning theory and student concept formation. Cognitive learning theory prioritizes students' cognitive or intelligence through a learning process. When students understand what they have gained from learning, they can shape their personality to be better and can understand their condition so that they can form a perfect self-concept. Then, several schools still use cognitive learning theory to form students' concepts.